North Korea: The last transition economy? - Koen, Vincent (OECD Economics Department Working Papers, 2020)
The North Korean economy has been a statistical black hole for decades but is undergoing substantial transformations. Rapid post-war industrialisation was not sustained beyond the mid-1960s and South Korea's economy far outpaced North Korea's during the next three decades, during which trend growth declined and turned negative as Soviet support ended and the terms of trade with China became less friendly. Today, GDP in North Korea is reportedly lower than in 1990, notwithstanding a larger population, and gross national income per capita is probably down to only a tiny fraction of South Korea's